2022
DOI: 10.1029/2022wr031977
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns and Quantification of Lacustrine Groundwater Discharge Determined Based on 222Rn

Abstract: Lakes are widely distributed worldwide and have great economic, environmental, and ecological importance (Zedler & Kercher, 2005). However, under increasing anthropogenic stress, eutrophication has become pervasive in many lakes, with ∼63% of lakes being identified as "eutrophic" in the trophic state classification system (Wang et al., 2018). Groundwater is a component that has long been overlooked in the study of the hydrological cycle and eco-environment of lakes. Recent investigations have shown that lacust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Almost all lakes interact with groundwater (Ahmadi et al, 2018; Boreux et al, 2021; Cohen et al, 2016; Winter, 1999). The past investigations have shown that the nutrient concentration via groundwater could be several orders of magnitude higher than that of surface water input (Boreux et al, 2021; Lewandowski et al, 2015; Sun et al, 2022), so the degree of which lakes interact with groundwater strongly affects the water balance and aquatic chemistry as well as aquatic biota in lake water and groundwater (Lewandowski et al, 2015; Rosenberry et al, 2015). However, the importance of hydrological connectivity has usually been ignored due to the unobservable process of lake–groundwater interaction (Chen & Tian, 2021; Kummu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Almost all lakes interact with groundwater (Ahmadi et al, 2018; Boreux et al, 2021; Cohen et al, 2016; Winter, 1999). The past investigations have shown that the nutrient concentration via groundwater could be several orders of magnitude higher than that of surface water input (Boreux et al, 2021; Lewandowski et al, 2015; Sun et al, 2022), so the degree of which lakes interact with groundwater strongly affects the water balance and aquatic chemistry as well as aquatic biota in lake water and groundwater (Lewandowski et al, 2015; Rosenberry et al, 2015). However, the importance of hydrological connectivity has usually been ignored due to the unobservable process of lake–groundwater interaction (Chen & Tian, 2021; Kummu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the importance of hydrological connectivity has usually been ignored due to the unobservable process of lake–groundwater interaction (Chen & Tian, 2021; Kummu et al, 2014). Recent research has demonstrated that accurately quantifying the exchange rate between lake and groundwater is a prerequisite for assessing the derived nutrient load of lake water and surrounding groundwater (Ferencz et al, 2019; Lewandowski et al, 2015; Rosenberry et al, 2015; Sun et al, 2022; Welch et al, 2013). Therefore, it is important to study the lake–groundwater interaction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations